The Application of Immunoglobulins Immune Response in the Discovery and Development of Safe Therapeutic Agents: A Review Article - Yilkal, Tariku Belay (Journal of Advanced Pharmaceutical Science And Technology, 2024)
Background Immunoglobulins are bio-receptors found embedded in the cell membrane with a biological role that detects the harmful molecules of a test compound. These bio-receptors interface between a biological system and its external environment that transduce information to the effector via intermediate messengers in which its response efficiency usually exhausts at high doses of exposure to external stimuli. The purpose of this review article is, therefore, to elaborate on the computational method for systemic biology which was designed to convert qualitative pharmacological data into the quantitative one that might help to determine the toxicity of a test compound. Methods First, acute toxicity studies using different levels of doses prepared from each test compound have been conducted on Balb c mice. Then, blood specimens from the tail and facial veins of each sampled Balb c mouse were collected 3 days before dosing as a reference test and 4 hr after dosing for comparison. The changes in the efficiency of immunoglobulins immune response (ΔIg) after dosing were determined using quantitative immunoassay and the body’s response against the dose as the toxic reaction rate (r) and the toxic severity (s) were finally determined using computational methods as r=d/t-ΔIg mg/sec and (s=r/w×100) %/sec respectively, where (w) represents the body weight of a study animal, (t) represents the period of time at which undesirable bio-physiological responses manifested on treated study animals and (ΔIg) represents the changes in the concentration of immunoglobulins in blood serum after dosing. Results The results of different studies revealed that the dose has never limited the toxic property of a test compound but the length of time at which the undesirable side effect was manifested on study animals. The period of time at which adverse effects manifested on treated Balb c mice was inversely related to the amount of dose administered in the oral route. The higher the dose of the administered test compound, the shorter the period of time at which the undesirable side effect was manifested on treated Balb c mice. This means that the adverse effect of test compounds was not because of the dose but rather due to its toxic reaction rate which ultimately determined the toxic severity in the natural process of treated Balb c mice. Balb c mice treated with a dose whose toxic reaction rate was ≤ 0 survived from death whereas Balb c mice treated with a dose that had a toxic reaction rate of > 0 died at different lengths of time after dosing depending on the toxic severity of a test compound. It could be a scientific fact to declare that a test compound is safe when the toxic reaction rate (r) and toxic severity (s) of a dose is ≤ 0 and toxic when it is > 0 in the natural processes of a study animal.
Keywords: Biological sensitivity; bio-receptors; response efficiency